Crystallographic Texture Analysis of As-Built and Heat-Treated Ti6Al4V (ELI) Produced by Direct Metal Laser Sintering - Muiruri, Amos; Maringa, Maina; Du Preez, Willie (Crystals 2020, 10, 699, 2020)
This paper reports on an investigation of crystallographic texture of as-built and heat-treated Ti6Al4V (ELI) produced by direct metal laser sintering (DMLS). The texture analyses were conducted using electron backscatter di raction (EBSD). The -phase texture from the obtained EBSD data was ascertained based on a reconstruction method using the Automatic Reconstruction of Parent Grain for EBSD data (ARPGE) program. A significant improvement of the maximum intensity of the texture from the pole figure was also noted upon heat treatment. The as-built samples and samples heat-treated just below the ! transformation temperature showed a stronger fibrous texture of the reconstructed -grains with the h100i directions almost parallel to the build direction. The alignment of the fibrous texture in the build direction disappeared after heat treatment above the ! -grain transformation temperature.
Article
Keywords: Texture; Direct metal laser sintering; Electron backscatter diffraction; Pole figure; Reconstruction; Variants